EFFECT OF RADIATION ON MORPHOLOGICAL CHARACTERS OF DIFFERENT CULTIVARS OF LILIUM AND GENETIC ANALYSIS OF MUTANTS THROUGH MOLECULAR MARKERS - F. Aslam; S. Naz; S. Javed (Journal of Animal and Plant Sciences, 2016)
Morphological parameters and RAPD (Random amplified polymorphic DNA) markers have been used to evaluate the effect of gamma radiation on different varieties of Lilium plant. In vivo treated plants were studied to observe the alternations in growth parameters.Change in plant morphology in aspect of flower morphology (flower colour and shape), leaf length, leaf width, shoot length and number of leaves per plant was detected. Treated plants showed significant alterations in different morphological traits as contrast to control plants were further analyzed by using RAPD markers. Total no. of 101 amplified products were obtained by using 11 polymorphic RAPD primers. The genetic similarity among the 4 Lilium parent varieties and their mutant genotypes ranged from 0.14-0.34 in V4 (Samur La pink), 0.08-0.42 in V5 (Heaven White), 0.11-0.38 in V6 (Golden Tycon yellow) & 0.14-0.38 in V8 (orange colour Liliy). It is concluded that RAPD practice could be effectively applied to the newly Lily variants and can make a distinction among the mutants from their parents.
Keywords: Lilium; Gamma radiation; Morphology; RAPD